Derecho Penal internacional: entre garantismo y eficientismo - Restrepo Montoya, Hugo A. (2023)
Modern criminal law conceived of its subject matter as not universal, marked by spatial, personal, and temporal limits. However, the current globalization of criminal law modifies such a paradigm: for instance, it is now understood that a part of criminal law is no longer limited, and that, instead, it is universal, not bound by space, and timeless. This article purports to find the philosophical foundations of the effort to create an International Criminal Law, by defining some international crimes; furthermore, it tries to understand where the Rome Statute fits in the tension between criminal guarantees and criminal efficiency, a tension currently experienced by criminal law.